Acoustic field measurements using a PVDF foil hydrophone - G. ŁYPACEWICZ; A. NOWICKI; R. TYMKIEWICZ; P. KARŁOWICZ; W. SECOMSKI (Archives of Acoustics, 2014)
This study was concerned with a membrane, pdvf foil and double-screened hydrophone, manufactured by Sonic Technologies, USA. Using the producer's data in the form of discrete data, power functions, describing the input impedance and the sensitivity of the hydrophone, depending on the frequency, were found. This made it possible to represent the measuring system in the form of a equivalent circuit containing a pressure source, a transformer which converted the acoustic pressure into the electric intensity (the hydrophone sensitivity), the hydrophone impendance, an additional coaxial cable and the input receiver impedance. The impacts of the receiver impedance and that of the additional cable on the accuracy of measurements of the acoustic pressure using a hydrophone were subsequently investigated. As an example, an ultrasonographic measurement using the hydrophone in question was cited.